Improving News Text Writing Skills Through Problem-Based Learning Model in Sixth Grade Students - Mustaqim, Aris (Jurnal Pena Ilmiah, 2023)
This research is a classroom action research aimed at describing the improvement in news text writing skills of sixth-grade students using a problem-based learning (PBL) model assisted by images and videos. The research consists of two cycles, each conducted in two meetings. The subjects of this research were 27 sixth-grade students at an elementary school in Bandung City. The results showed that the application of the problem-based learning model assisted by images and videos improved the news text writing skills, with an increase in the average score from 69.8 to 87. The learning process can be considered successful as the students overall met the minimum competency criteria (KKM). The students also responded very positively to learning news text writing through the application of the problem-based learning model assisted by images and videos, with a score of 55.2. Penelitian ini merupakan penelitian tindakan kelas (classroom action research) yang bertujuan mendeskripsikan peningkatan keterampilan menulis teks berita siswa kelas VI menggunakan model pembelajaran berbasis masalah (problem based learning, PBL) dengan berbantuan media gambar dan video. Penelitian ini terdiri dari dua siklus dan setiap siklus dilaksanakan dalam dua kali pertemuan. Subjek penelitian ini adalah 27 siswa kelas VI di sebuah sekolah dasar Kota Bandung. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran berbasis masalah berbantuan media gambar dan video meningkatkan keterampilan menulis teks berita dengan peningkatan skor rata-rata keterampilan menulis teks berita sebesar 69,8 menjadi 87. Pembelajaran dapat dikatakan berhasil karena secara keseluruhan siswa telah memenuhi KKM. Siswa juga memberikan respons yang sangat positif dalam mengikuti pembelajaran teks berita melalui penerapan model pembelajaran berbasis masalah berbantuan media gambar dan video yakni dengan skor 55,2.